Influence of Workload, Personality, and Psychological Flexibility on Occupational Stress Among Medical Staff: A Fuzzy-Set Qualitative Comparative Analysis - Quan, Liming; Zhang, Yang; Jiang, Fugui; Liu, Ying; Lan, Yajia; Huang, Lei (Frontiers in Public Health, 2022)
Objective: During the COVID-19 pandemic, the occupational stress of medical staff has been a major issue. This study aimed to identify high-risk factor sets of occupational stress in medical staff using fuzzy-set qualitative comparative analysis (fs-QCA) and provides ideas for the prevention and intervention of occupational stress. Methods: A total of 1,928 medical staff members were surveyed and tested using the Acceptance and Action Questionnaire-II (AAQ-II), Occupational Stress Inventory-Revised edition (OSI-R), and Eysenck Personality Questionnaire-Revised Short Scale (EPQ-RSC). The fs-QCA was used to explore the high-risk factors for occupational stress among medical staff. Results: The psychological strain (PSY) score of the medical staff was 26.8±7.13, and the physical strain (PHS) score was 24.3±6.50. Low psychological flexibility score-introversion-high role overload, introversion-neuroticism-high role overload, and low psychological flexibility score-neuroticism were high-risk factor sets for PSY. Low psychological flexibility score-introversion-high role overload, low psychological flexibility score-introversion-neuroticism, low psychological flexibility score-neuroticism-high role overload, low psychological flexibility score-psychoticism-neuroticism, and psychoticism-neuroticism-high role overload were high-risk factor sets for PHS. Conclusion: There are different combinations of high-risk factors for occupational stress among the medical staff. For occupational stress intervention and psychological counselling, targeted and individualized health intervention measures should be implemented according to specific characteristic combinations of different individuals.